The devil you know… Familiarity, legitimacy, and religious mobility in pentecostalised Kenya - Gez, Y. N.; Droz, Y. (Cahiers d'études africaines, 2024)
The Kenyan Christian urban landscape is characterised by major concerns over religious deviance and by high rates of individual mobility. This article explores how Kenyan Christians experience their religious practice within this challenging environment. At the core of our argument lies the concept of familiarity/familiarisation, which views religious mobility in terms of accumulated exposures and which we explore in juxtaposition with the concept of religious legitimacy. We thus link moral religious considerations and negotiations with mobile trajectories, which at times turn towards new horizons (e.g. through “church visits”) and at times keep to the boundaries of the already-familiar (“circular mobility”) while staying on the lookout for narratives and rumours emerging from less familiar spaces. These reflections not only acknowledge the axial role of religious mobility within practitioners’ ongoing socio-religious orientation, but also draw attention to the invisible-yet-significant potential of their religious past.